Comprehensive analyses of the ARF gene family in cannabis reveals their potential roles in regulating cannabidiol biosynthesis and male flower development - Pan, Gen; Yang, Xiaojuan; He, Jiajia; Liu, Zhenyi; Chen, Fengming; Chen, Jiayi (Frontiers in Plant Science, 2024)
Background Cannabidiol (CBD), as an important therapeutic property of the cannabis plants, is mainly produced in the flower organs. Auxin response factors (ARFs) are play a crucial role in flower development and secondary metabolite production. However, the specific roles of ARF gene family in cannabis remain unknown. Methods In this study, various bioinformatics analysis of CsARF genes were conducted using online website and bioinformatics, quantitative real time PCR technology was used to investigate the expression patterns of the CsARF gene family in different tissues of different cannabis varieties, and subcellular localization analysis was performed in tobacco leaf. Results In this study, 22 CsARF genes were identified and found to be unevenly distributed across 9 chromosomes of the cannabis genome. Phylogenetic analysis revealed that the ARF proteins were divided into 4 subgroups. Duplication analysis identified one pair of segmental/whole-genome duplicated CsARF, and three pairs of tandemly duplicated CsARF. Collinearity analysis revealed that two CsARF genes, CsARF4 and CsARF19, were orthologous in both rice and soybean. Furthermore, subcellular localization analysis showed that CsARF2 was localized in the nucleus. Tissue-specific expression analysis revealed that six genes were highly expressed in cannabis male flowers, and among these genes, 3 genes were further found to be highly expressed at different developmental stages of male flowers. Meanwhile, correlation analysis between the expression level of CsARF genes and CBD content in two cultivars ‘H8’ and ‘Y7’ showed that the expression level of CsARF13 was negatively correlated with CBD content, while the expression levels of six genes were positively correlated with CBD content. In addition, most of CsARF genes were responsive to IAA treatment. Conclusion Our study laid a foundation for the further studies of CsARFs function in cannabis, and provides candidate genes for breeding varieties with high CBD yield in cannabis production.